Composition and structure community of arthropods in organic and conventional arabica coffee plantation. (May 2019) - Husni,; Jauharlina,; Saifullah,
Abstract: A series of observation was conducted in Arabica coffee plantation, in Bener Meriah Regency of Aceh Province, Indonesia. We investigated the difference of arthropods biodiversity in Arabica coffee plantation between organic and conventional farming system. The result showed that the composition and structure community of the arthropods in organic coffee plantation were higher than those of the conventional ones. In coffee plantations that are managed organically the number of orders and family of arthropod are far more than conventional ones, namely (10 orders, 65 families) and (7 orders, 31 families) respectively. Some of the arthropod species that were collected potentially have a role as predators or parasitoids of insect pests on the coffee plant. On organic coffee, fields were found 7 orders, 20 families and 45 species of arthropod that were potential as natural enemies of insect pests, while in conventional land only 4 orders, 13 families and 32 species were found. The others have a role as decomposers, pollinators, etc. The result of this research indicated that the organic farming system of coffee plantation has played an important role in maintaining the biodiversity of the insects in a coffee plantation.